MORFOLOGI ABU LIMBAH PENGOLAHAN KAYU SEBAGAI BAHAN DASAR GEOPOLIMER UNTUK MATERIAL PENYANGGA TAMBANG BAWAH TANAH - Jance M. Supit (INTAN Jurnal Penelitian Tambang, 2018)
Geopolymer is made from materials that are both natural polozan and artificial pozolan. Pozolan materials contain silica (SiO2) and alumina (Al2O3). Both of these compounds can be found as natural materials (such as metakaolin, and volcanic material), as well as waste (eg fly ash, husk ash). The potential of forest products in the form of wood in Papua, especially Manokwari Regency, is very abundant, as well as its utilization efforts. The processing or utilization of wood results in the solid waste in the form of pieces, leftovers and wood sawdust. This study aims to explain the geopolymer morphology of wood processing waste ash in Manokwari, from which it can be used as buffer material. By using SEM-EDX in the analysis, the results showed that the size of ash grain of wood processing waste was ≤100 µm (from Merbau wood or mixed wood). The elements contained in the ashes of merbau wood waste consist of O, Ca, C, Si, K, Mg, Al, Cu, Fe, and S. Meanwhile, mixed wood waste ash contains O, Ca, C, Si, K, Mg, Al, Fe, Na, and S. Wood processing waste in Manokwari Regency has the potential to be used as the basis for making geopolymer because it dominantly contains Si and Al elements.